The T-statistically convergent sequences are not an FK-space - Jeannette Kline (International Journal of Mathematics and Mathematical Sciences)
In ths note show that under certain restrictions on a nonnegative regular summability matrix T, the space of T-statistically convergent sequences cannot be endowed with locally convex FK topology.